2013
DOI: 10.1038/aja.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylase 2 mitigates profibrotic TGF-β1 responses in fibroblasts derived from Peyronie's plaque

Abstract: Epigenetic modifications, such as histone acetylation/deacetylation, have been shown to play a role in the pathogenesis of fibrotic disease. Peyronie's disease (PD) is a localized fibrotic process of the tunica albuginea, which leads to penile deformity. This study was undertaken to determine the anti-fibrotic effect of small interfering RNA (siRNA)-mediated silencing of histone deacetylase 2 (HDAC2) in primary fibroblasts derived from human PD plaque. PD fibroblasts were pre-treated with HDAC2 siRNA and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
2
32
0
1
Order By: Relevance
“…In order to determine if inhibition of HDAC2 would limit the profibrotic response to TGFβ signaling in human PD plaques, Ryu et al used RNA interference (RNAi) via small interfering RNA (siRNA) targeting HDAC2, comparing PD plaque-derived fibroblasts to control fibroblasts transfected with nonspecific scramble siRNA. 94 Protein expression levels of plasminogen activator inhibitor 1 (PAI1), fibronectin, collagens I and IV, smooth muscle α-actin, and HDAC2 were assessed using Western blot following stimulation with TGFβ. The authors observed a 60% reduction in HDAC2 expression in PD plaque-derived fibroblasts transfected with the HDAC2-targeted siRNA, with similar reductions in expression of PAI1, fibronectin, collagens I and IV, and smooth muscle α-actin.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…In order to determine if inhibition of HDAC2 would limit the profibrotic response to TGFβ signaling in human PD plaques, Ryu et al used RNA interference (RNAi) via small interfering RNA (siRNA) targeting HDAC2, comparing PD plaque-derived fibroblasts to control fibroblasts transfected with nonspecific scramble siRNA. 94 Protein expression levels of plasminogen activator inhibitor 1 (PAI1), fibronectin, collagens I and IV, smooth muscle α-actin, and HDAC2 were assessed using Western blot following stimulation with TGFβ. The authors observed a 60% reduction in HDAC2 expression in PD plaque-derived fibroblasts transfected with the HDAC2-targeted siRNA, with similar reductions in expression of PAI1, fibronectin, collagens I and IV, and smooth muscle α-actin.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…Alterations of apoptosis gene expression observed in PD plaques have been allegedly involved in the fibrosing process following a status of local inflammation [21], as they may eventually result in abnormally prolonged fibroblast activity and survival. Likewise, epigenetic modifications seem to play a role fostering fibrosis [22]. Preclinical data also showed how local antigen‐driven immune response at the level of the tunica albuginea, such as the case of a rat tunica albuginea allograft, induces similar alterations to those observed in PD plaques [23].…”
Section: Introductionmentioning
confidence: 91%
“…39 Recent studies have also shown that both HDAC2 silencing and inhibition induce regression of fibrotic formation in Peyronie’s disease models. 40,41 Using mutant fibroblasts that are HDAC2-deficient, Zimmerman and collaborators demonstrated a lack of response to insulin-like growth factors (IGFs) when compared to wild type cells, showing a potential link between HDACs and IGFs. 34 Mice models lacking HDAC1 and with a single HDAC2 allele develop a lethal pathology within 3 months, likely due to neoplastic transformation of immature T cells.…”
Section: Class I Hdacsmentioning
confidence: 99%